The Transition to Outcome-Based Education (OBE): A Phenomenological Study of Islamic Religious Education Lecturers - Purnomo; Budiyono Saputro; Miftahuddin (Journal of Education and Religious Studies, 2026)
This study aims to explore in depth the understanding, challenges, and support experienced by Islamic Religious Education (IRE) lecturers during the transition to the Outcome-Based Education (OBE) curriculum, which often faces skepticism and technical challenges. This study employs a qualitative approach with a phenomenological design to explore the meaning of the lived experiences of four lecturers from the IRE study program. Data were collected through in-depth interviews and analyzed using a framework analysis based on Kurt Lewin's Three Phases of Change Model (Unfreeze, Change, Refreeze), and enriched with Hochschild's Emotional Labor Theory. The research findings indicate that the OBE transition experienced a systemic failure in the Refreeze Phase. The Unfreeze Phase successfully created cognitive dissonance about the need for change, but immediately triggered negative emotional labor such as "anxiety," "confusion," and "burden." The Change Phase was hindered by dominant restraining forces, particularly the difficulty of designing assessments (considered "the most difficult"), increased workload, and a lack of systemic training support. Consequently, the Refreeze Phase failed; OBE is "not yet established" and is perceived as merely a "momentary trend" of administrative compliance ("discharging obligations"), not as an internalized pedagogical change.